Effects of R&D policy choice on accounting performance and market value. (27th June 2016) - Wang, Yanni; Du, Rong; Koong, Kai S.; Fan, Weiguo
Abstract : Using primary data that was gathered from the annual reports of companies listed in the Chinese Stock Exchanges, this study analyzes and compares the different effects of R&D policy choice on their accounting performances and market values. For the period 2007 through 2014, the results show that different R&D policy choices provided different implications in firm value and firm strategy to the market. Specifically, the firms choosing to capitalize their R&D investments have higher market value, implying that the strategy was focused on sustaining their long‐term development. On the contrary, the companies selecting to expense their R&D expenditure have higher accounting performance and the focus was on improving short‐term gains. The results of this study suggest that the policy choice on R&D capitalization and expensing is a trade‐off result between the accounting performance and the market value of a firm.